Hubungan Antara Intensitas Waktu Bermain Video Game dengan Kejadian Miopia pada Mahasiswa S1 Kedokteran Universitas Batam - Nurul Widiati; Luis Yulia; Muhamad Fauzan (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
blurring, difficulty seeing distant objects, and frequent squinting when looking at distant objects and in the eye. One of the most common refractive errors is myopia Methods :This research method isis an analytic observational, with a cross-sectional approach. The sample in this study were students of the 2018 Batam University Bachelor of Medicine study program with a total of 80 samples. And brought to the optician to fill out a questionnaire and an eye examination to see the incidence of myopia. The analytical test used is the chi square test. Results :The test results show that there is a significant relationship between the intensity of playing video games with the incidence of myopia in undergraduate medical students at the University of Batam Batch 2018. From the Chi Square results, a p-value of 0.000 is obtained, so H0 is rejected and Ha is accepted. Conclusion:Based on the results of this study can be Keywordsthere is a significant relationship between the intensity of playing video games with the incidence of myopia.